Exercise Ameliorates Diabetic Kidney Disease in Type 2 Diabetic Fatty Rats - Itaru Monno; Yoshio Ogura; Jing Xu; Daisuke Koya; Munehiro Kitada (MDPI AG, 2021)
Lifestyle improvement, including through exercise, has been recognized as an important mode of therapy for the suppression of diabetic kidney disease (DKD). However, the detailed molecular mechanisms by which exercise exerts beneficial effects in the suppression of DKD have not yet been fully elucidated. In this study, we investigate the effects of treadmill exercise training (TET) for 8 weeks (13 m/min, 30 min/day, 5 days/week) on kidney injuries of type 2 diabetic male rats with obesity (Wistar fatty (fa/fa) rats: WFRs) at 36 weeks of age. TET significantly suppressed the levels of albuminuria and urinary liver-type fatty-acid-binding protein (L-FABP), tubulointerstitial fibrosis, inflammation, and oxidative stress in the kidneys of WFRs. In addition, TET mitigated excessive apoptosis and restored autophagy in the renal cortex, as well as suppressed the development of morphological abnormalities in the mitochondria of proximal tubular cells, which were also accompanied by the restoration of AMP-activated kinase (AMPK) activity and suppression of the mechanistic target of rapamycin complex 1 (mTORC1). In conclusion, TET ameliorates diabetes-induced kidney injury in type 2 diabetic fatty rats.